The Impact of Structural Break(s) on the Validity of Purchasing Power Parity in Turkey: Evidence from Zivot-Andrews and Lagrange Multiplier Unit Root Tests - Hakan Kum (International Journal of Economics and Financial Issues, 2012)
This study examines the validity of the purchasing power parity (PPP) in Turkey for annual data from 1953 to 2009. While results from both the ADF unit root and the DF-GLS unit root test indicate mixed results, PPP holds for Turkey with the presence of structural breaks which are obtained by Zivot and Andrews and Lagrange Multiplier unit root tests.